2012
DOI: 10.7860/jcdr/2012/4347.2577
|View full text |Cite
|
Sign up to set email alerts
|

A Type III Dens Invaginatus with Unusual Helical CT and Histologic Findings: A Case Report

Abstract: Dens Invaginatus (DI) is a rare developmental anomaly which affects the tooth, which shows an infolding of enamel and dentine which extends into the pulp chamber and sometimes into the root. The aim of this case report was to describe its radiographic findings, to emphasize the bizarre morphology and the difficulties which are encountered in the diagnosis by using conventional radiographic techniques and the importance of computed tomography as a valuable diagnostic aid. Dens Invaginatus is clinically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 4 publications
(4 reference statements)
0
16
0
2
Order By: Relevance
“…Because invaginated enamel is a developmental abnormality of the enamel organ, we expected to find the reduced enamel epithelium, which may explain resistance to enamel caries in invagination. Mishra et al emphasized their report about the unusual hyperdense enamel of the invagination, however there was no histologic correlation for it 15) . We first report this interested phenomenon to verify in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because invaginated enamel is a developmental abnormality of the enamel organ, we expected to find the reduced enamel epithelium, which may explain resistance to enamel caries in invagination. Mishra et al emphasized their report about the unusual hyperdense enamel of the invagination, however there was no histologic correlation for it 15) . We first report this interested phenomenon to verify in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Mishra et al stated the hyperdense CT number at the invaginated enamel surface in a case report of type III DI. However the ground section of the invaginated enamel showed hypomineralized 15) . The μCT analysis of the DI teeth in our study revealed extremely low MD in the invaginated enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Dens invaginatus (Dİ) veya dens in dente biyolojik mineralizasyon oluşmadan önce diş kuronunun invaginasyonunun neden olduğu nadir gelişimsel bir malformasyondur (1,2). Dİ ilk olarak Baume tarafından 1874'de tanımlanmıştır (3,4). Dens in dente, invagine odontoma, genişlemiş kompozit odontoma, tooth inclusion ve dentoid in dente gibi isimlerle de tanımlanmıştır (2,4).…”
Section: Introductionunclassified
“…This can occur both in the crown as the root and may involve the pulp chamber or root canal, resulting in deformity in their morphology (Mishra et al, 2012). According to the literature, the frequency varies from 0.04 % to 10 % (Hovland, 1977;Hülsmann;Pradeep et al;Jaya et al;Brooks & Ribera, 2014;Ceyhanli et al, 2014;Kaya-Büyükbayram et al;Teixeidó et al;Zubizarreta Macho et al, 2015), predominating in female (3:1) (Alani & Bishop, 2008;Mishra et al), affecting either the deciduous or the permanent dentition (Alani & Bishop; Jaya et al).…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the frequency varies from 0.04 % to 10 % (Hovland, 1977;Hülsmann;Pradeep et al;Jaya et al;Brooks & Ribera, 2014;Ceyhanli et al, 2014;Kaya-Büyükbayram et al;Teixeidó et al;Zubizarreta Macho et al, 2015), predominating in female (3:1) (Alani & Bishop, 2008;Mishra et al), affecting either the deciduous or the permanent dentition (Alani & Bishop; Jaya et al). The most affected permanent teeth are the maxillary lateral incisors (Oehlers, 1957;Cohenca & Berg, 2013;Jaya et al;Kfir et al;Brooks & Ribera;Ceyhanli et al;Kaya-Büyükbayram et al, Muppa et al;Vier-Pelisser et al, 2014;Capar et al;Zubizarreta Macho et al;Nosrat & Schneider), frequently bilaterally (43 %) (Hülsmann; Durack & Patel; Mishra et al; Pradeep et al; Cohenca & Berg; Jaya et al; Zubizarreta Macho et al), followed by central incisors, including supernumerary teeth, maxillary cuspids, mandibular incisors, and mandibular premolars affecting the molars rarely (Oehlers; Cohenca & Berg; Jaya et al), rarely affecting the molars (Bansal & Pratap, 2010;Matsusue et al, 2011).…”
Section: Introductionmentioning
confidence: 99%